The Predictive Effect of Alexithymia towards the Metacognition and Emotional Distress in University Students - Anjum, Razia; Shafique, Rukhsar; Latif, Muhammad (Annals of Human and Social Sciences, 2024)
The main objective of the study is to explore the relationship of alexithymia with metacognition and emotional distress in university students. Student’s inability to recognize and express their feelings, restricted imagination and an outwardly focused way of thinking make are core components of alexithymia that make vulnerable to experience emotional distress and leads toward the overthinking. Although alexithymia is common among university students, but there is no specific diagnostic criterion for it. Borderline symptoms of alexithymia often misinterpreted. Students suffering from alexithymia are prone to experience other mental health issues. Cross sectional correlational research design was used, Data comprised on 152 male, 152 female university students with age range of 18-24 years, selected from different public and private universities of Sialkot city. A self- developed demographic sheet with Toronto Alexithymia Scale, Metacognition and Perceived Emotional Distress was administered on participants. Descriptive and inferential statistics was used to analyse the data, study results indicated the alexithymia as a strong predictor of metacognition and emotional distress in university students. Moreover the mean differences in alexithymia across first- eight semesters was found. The impact of alexithymia and the role of metacognition on emotional distress may be better understood with the support of longitudinal studies. Future research must be conducted using a clinical sample in order to draw conclusions about the clinical implications.